Hedging in Lithuanian and English research articles: a cross – disciplinary and cross – linguistic study - Šinkūnienė, Jolanta (Kalbotyra, 2008)
Hedging is a linguistic strategy frequently employed in scientific writing to diminish the author‘s commitment to the accompanying proposition and to mitigate claims, thus presenting a proposition as a possibility or probability rather than a fact. This article describes the results of a pilot study on the frequency and variety of hedging devices in Lithuanian and English research articles in two different disciplines (linguistics and medicine). The study is limited to lexical hedges only. The results of a cross – disciplinary study demonstrate that in the field of medicine, researchers tend to hedge less and hence are much more determined in their claims than linguists in both languages. The cross – linguistic study shows that English speaking researchers seem to use significantly more hedging devices than their Lithuanian speaking colleagues in both disciplines. The variety of hedges used in English was also wider than in Lithuanian. Most frequently used hedges in both languages in linguistic articles were adverbs, whereas in medical articles it was modal verbs.